Prognostic value of perihematomal edema for prediction early lethal outcome after spontaneous supratentorial intracerebral hemorrhage - Kuznietsov, A. A.; Konovalova, D.; Кузнєцов, Антон Анатолійович (Запорізький державний медичний університет, 2016)
Background: Elaboration of computer tomographic criteria to predict early lethal outcome (ELO) after spontaneous supratentorial intracerebral hemorrhage (SSICH) is a very important and relevant in modern angioneurology that can help the practicioners to identify candidates for neurosurgical intervention and improve effectiveness of treatment approaches. We therefore verified the prognostic value of perihematomal edema for prediction ELO after SSICH.